Acardiac Twin (Delta Medical College Journal, 2014)
Acardiac anomaly is a rare complication of multiple pregnancies. It is a hemodyamically disadvantaged nonviable twin which occurs in association with a twin reversed arterial perfusion sequence (TRAP). In TRAP, blood flows from an umbilical artery of the pump twin in reverse direction into umbilical artery of the perfused (or acardiac) twin via an arterial to arterial (AA) anastomosis. Its blood is poorly oxygenated and results in variable degrees of deficient development of the head, heart, and upper limb structures. The lower half of the body is usually better developed, which may be explained by the mechanism of perfusion. The pump twin is at risk of heart failure and problems related to preterm birth with a reported mortality of 50-75%. We present a case of multiple pregnancy with acardiac twin in a 26 year old lady with gestational diabetes mellitus. During ante natal check up several ultrasonographic (USG) screening showed twin pregnancy with one healthy fetus and the other fetus with inconspicuous anatomy and structure. Repeat USG at 36th week of gestation diagnosed twin pregnancy with acardiac twin. Strikingly the pump twin did not develop the usual complications and was delivered by cesarean section at 37th week of gestation. DOI: http://dx.doi.org/10.3329/dmcj.v2i2.20529 Delta Med Col J. Jul 2014; 2(2): 77-80